Media-mediated relationships straight and gay, mainstream and alternative perspectives - Fuller, Linda K. (Haworth popular culture, 1996)
As straight and gay people alike live in a time of reluctant commitments, a period of playtime, and the Age of AIDS, the time has come to chronicle the role of mass communication in our search for interpersonal connections. Media-Mediated Relationships investigates the historical, economic, psychological, and sociocultural ramifications of the print and broadcast media, motion pictures, music, and new communications technologies (computers, video, interactive media, virtual reality, phone sex) in terms of both our individual and societal concerns. Media-Mediated Relationships provides a barometer for better understanding the many "singles" and others searching for meaning and relationships in the sociocultural milieu of the 1990s and beyond.